Exploring harmful traditional practices and its associated factors among puerperal mothers who delivered in public health facilities in southwestern Ethiopia - Endale Tamiru Burayu; Bekem Dibaba Degefa (Scientific Reports)
Abstract Harmful traditional practices are deeply ingrained beliefs and behaviors within a society that significantly impact the well-being of mothers and children. In Ethiopia, there is limited awareness and comprehension concerning the prevalence of harmful traditional practices in the puerperal period. The underlying reasons for engaging in harmful cultural practices during this period at the community level remain inadequately studied. The main aim of this research is to investigate the prevalence of harmful traditional practices during the puerperal period and its associated factors in public health facilities of southwestern Ethiopia, 2023. A mixed-methods community-based cross-sectional approach was undertaken from June 1st to July 31st, 2023. The study utilized the 24 kebeles in the Ilubabor and Buno Bedele Zones of Southwest Ethiopia. Three hundred twenty puerperal mothers in selected kebeles found in Ilubabor and Buno Bedele zones met inclusion criteria during the data collection period. We used a pretested semi-structured questionnaire, supplemented by in-depth interviews and focused group discussions with purposively selected 18 mothers. We utilized backward multiple logistic regressions were utilized to evaluate the interplay between various factors, with statistical significance set at a P-value below 0.05. This finding disclosed that the prevalence of harmful traditional practices during the puerperal period was 76.3%. Factors such as educational status (AOR = 3.47, CI = 1.57–9.27), rural residency (AOR = 2, CI = 1.51–4.88), absence of antenatal care in the last pregnancy (AOR = 6.42, CI = 2.33–8.74), and the place of delivery for the most recent child (AOR = 1.7, CI = 1.15–4.07) were significantly associated with these practices. The findings underscore a substantial prevalence of harmful traditional practices among mothers during the puerperal period. It is imperative for the Zonal Health department, in collaboration with relevant stakeholders, to actively combat these practices within rural communities and healthcare facilities.